MO049FUNCTIONAL IMPORTANCE OF MAPKBP1 PROTEIN DOMAINS IN NEPHRONOPHTHISIS. (29th May 2021) - Hartig, Christin; Schönauer, Ria; Sewerin, Sebastian; Ertel, Anastasia; Jin, Wenjun; Hantmann, Elena; Saunier, Sophie; Benmerah, Alexandre; Halbritter, Jan
Abstract: Background and Aims: Nephronophthisis is an autosomal-recessive kidney disease that accounts for a significant proportion of end-stage renal disease (ESRD) in childhood, adolescence and early adulthood. Biallelic pathogenic variants in MAPKBP1, encoding the c-Jun N-terminale kinase (JNK)-binding protein 1, are associated with development of Nephronophthisis and subsequent chronic kidney disease (CKD) (Macia et al, AJHG, 2017). We recently characterized MAPKBP1 as microtubule-associated protein that is able to localize to centrioles and the base of primary cilia depending on dimerization via its C-terminal coiled-coil domain (Schönauer et al, Kidney Int, 2020). However, the physiological function of its N-terminal WD40 and intermediate JNK-binding domain is still poorly understood. By in vitro comparison of artificial domain deletions with known and novel patient variants, we aim at pinpointing functional consequences of pathogenic MAPKBP1 in cilia and cell cycle control. Method: N-terminally GFP-tagged MAPKBP1 constructs with either full-domain deletions or patient-derived variants were expressed in non-ciliated HeLa and ciliated H69 cells for fluorescence microscopy studies. Furthermore, RNA-seq analysis using primary patient cells was conducted to investigate differentially regulated molecular pathways compared to healthy control individuals. Results: Immunofluorescence microscopy revealed inappropriate intracellular localization upon single or combined deletion of any MAPKBP1 protein domain. Compared to wild type, all deletion variants showed reduced intensity at the centrosome and ciliary base. Despite preserved dimerization ability, loss of the intermediate JNK-binding domain (JBD) most effectively abolished centrosomal or ciliary targeting, whereas loss of the N-terminal WD40-domain induced strongest mitotic aberrations. Unlike wild type, both, artificial and patient-derived truncating variants were able to enter the nucleus. RNA-seq analysis using primary patient fibroblasts with varying C-terminal truncations will allow important insights into common gene expression profiles unveiling consequences of aberrant intracellular trafficking. Conclusion: In the present work, we demonstrate that all protein domains are indispensable for appropriate MAPKBP1 intracellular localization and function. Most of clinically reported patient variants exhibiting C-terminal truncation of varying lengths resulted in comparable intracellular behavior in presence of an intact N-terminal WD40 domain. Surprisingly, deletion of the JNK-binding domain alone aggravated functional disturbances hinting at a prominent regulatory role of this protein part interdepending with dimerization. Further insights into domain-specific functions will explain molecular disease mechanisms of MAPKBP1.